Activation of the sympathetic-adrenal-medullary system increases DNA damage during the transition to captivity. - Kilgour, Denyelle A.; Romero, L Michael (Tufts University. Tisch Library., 2025)
Prior work has demonstrated that both acute and chronic stress can increase the number of double-stranded breaks detected in DNA and that the hypothalamic-pituitary-adrenal axis is the primary driver of increases in DNA damage during acute stress. However, the role of the sympathetic-adrenal-medullary (SAM) system in causing the increase in DNA damage observed during chronically stressful situations such as the transition to captivity is less well understood. We tested the hypothesis that chronic SAM activation via catecholamine release increases DNA damage by administering a beta-blocker to wild house sparrows (Passer domesticus) at capture and throughout the day during the first few days of captivity. We quantified double-stranded DNA breaks throughout the 2-week transition to captivity. We found that immediately following the treatment period, both control and beta-blocker-treated birds had similar levels of DNA damage, but after 2 weeks in captivity, treated birds had lower levels of damage. These data suggest that SAM system activation plays a role in creating the previously observed patterns of DNA damage during chronic stress and that suppressing SAM effects may lead to faster recovery and less damage overall, thereby easing the transition to captivity for wild animals.; Funding for open access publishing provided by the Tisch Library Open Access Publishing Fund.